Analysis of trace metal distribution in plants with lab-based microscopic X-ray fluorescence imaging - Mijovilovich, Ana; Morina, Filis; Bokhari, Syed Nadeem; Wolff, Timo; Küpper, Hendrik (Plant methods, 2020)
BACKGROUND: Many metals are essential for plants and humans. Knowledge of metal distribution in plant tissues in vivo contributes to the understanding of physiological mechanisms of metal uptake, accumulation and sequestration. For those studies, X-rays are a non-destructive tool, especially suited to study metals in plants. RESULTS: We present microfluorescence imaging of trace elements in living plants using a customized benchtop X-ray fluorescence machine. The system was optimized by additional detector shielding to minimize stray counts, and by a custom-made measuring chamber to ensure sample integrity. Protocols of data recording and analysis were optimised to minimise artefacts. We show that Zn distribution maps of whole leaves in high resolution are easily attainable in the hyperaccumulator Noccaea caerulescens. The sensitivity of the method was further shown by analysis of micro- (Cu, Ni, Fe, Zn) and macronutrients (Ca, K) in non-hyperaccumulating crop plants (soybean roots and pepper leaves), which could be obtained in high resolution for scan areas of several millimetres. This allows to study trace metal distribution in shoots and roots with a wide overview of the object, and thus avoids making conclusions based on singular features of tiny spots. The custom-made measuring chamber with continuous humidity and air supply coupled to devices for imaging chlorophyll fluorescence kinetic measurements enabled direct correlation of element distribution with photosynthesis. Leaf samples remained vital even after 20 h of X-ray measurements. Subtle changes in some of photosynthetic parameters in response to the X-ray radiation are discussed. CONCLUSIONS: We show that using an optimized benchtop machine, with protocols for measurement and quantification tailored for plant analyses, trace metal distribution can be investigated in a reliable manner in intact, living plant leaves and roots. Zinc distribution maps showed higher accumulation in the tips and the veins of young leaves compared to the mesophyll tissue, while in the older leaves the distribution was more homogeneous.
Keywords: Capsicum annuum; Hyperaccumulator; Arabidopsis halleri; Glycine max; Leaf age; Micro X-ray fluorescence; Noccaea caerulescens; Zinc; Root; Micronutrients